2008
DOI: 10.3141/2051-01
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Aging Characteristics of Polyphosphoric Acid-Modified Asphalts

Abstract: An experiment involving three neat asphalts and their mixtures with 1.5 wt % of polyphosphoric acid (105%) was conducted to investigate the effect of polyphosphoric acid (PPA) on the long-term aging characteristics of asphalt binders. Analytical techniques including dynamic shear rheometry, Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance (NMR) spectroscopy were performed on unaged and aged PPA-modified asphalts. Rheological properties of unaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…The optimum percentages of each additive and its mixing temperature with binder have already been obtained and proposed in previous research studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The main specifications of each modifier are briefly outlined in the following.…”
Section: Mixing Procedures Of Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimum percentages of each additive and its mixing temperature with binder have already been obtained and proposed in previous research studies [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The main specifications of each modifier are briefly outlined in the following.…”
Section: Mixing Procedures Of Additivesmentioning
confidence: 99%
“…PPA breaks the asphaltene agglomerates and creates the possibility for better distribution of asphaltene in the molten phase [28,29]. PPA is a mineral polymer in liquid form which is used in order to improve the rheological properties of the bitumen and the asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of phase measurement in prediction of performance is given importance in US -SHRP performance based specification. The permanent deformation of bituminous surface can be controlled by a minimum value of [G*]/sinδ in the high service temperature range 11 . A maximum value of [G*].sinδ in the medium temperature range is important to reduce the risk of fatigue cracking.…”
Section: Introductionmentioning
confidence: 99%
“…According to Masson, the existence of such areas is speculative, but not impossible. It has also been reported that after modification with PPA, no new chemical species, containing phosphorous compounds were formed in the bitumen-PPA mixture (Huang et al 2008 and.…”
Section: Introductionmentioning
confidence: 99%